3-Triethylammonium propane sulfonate ionic liquids for Nafion-based composite membranes for PEM fuel cells - Zanchet, Letícia; da Trindade, Letícia Guerreiro [UNESP]; Bariviera, William; Nobre Borba, Katiúscia M.; Santos, Rapher Donizete Moreira; Paganin, Valdecir Antonio; de Oliveira, Cristiane Pontes; Ticianelli, Edson Antonio; Martini, Emilse Maria Agostini; de Souza, Michèle Oberson (Springer Nature, 2020)
The 3-triethylammonium propane sulfonic (TEA-PS+) cation associated with the anion tetrafluoroborate, hydrogen sulfate or trifluoromethanesulfonate leads to the formation of the new protic ionic liquids (ILs) 3-triethylammonium propane sulfonic acid tetrafluoroborate (TEA-PS·BF4), 3-triethylammonium propane sulfonic acid hydrogen sulfate (TEA-PS·HSO4) and 3-triethylammonium propane sulfonic acid trifluoromethanesulfonate (TEA-PS·CF3SO3), respectively. These ILs are used to produce Nafion/IL composite membranes with 2.5, 5 or 10 wt% of IL. The results show that the IL addition improves the thermal stability, hydrophilicity and conductivity. Experiments performed with the Nafion/IL membranes in a single proton exchange membrane fuel cell at 100 °C indicate that the membrane containing 5 wt% of TEA-PS·HSO4 is the most efficient one producing an increase of the maximum current density of approximately 230% when compared to the pristine membrane.